Comparison of Cephalometric Measurements Between Hand Tracing and Digital Tracing Based on Android OneCeph - Tita Ratya Utari; Nur Izzatul Mujidah (Universitas Muhammadiyah Yogyakarta, 2023)
Lateral cephalometric radiographic examination is one of the supporting examinations in orthodontic treatment. Cephalometric measurements can be performed using hand tracing (manual) and digital methods. The digital method is widely preferred today due to its faster measurement, easy and safe storage, and can be sent anywhere easily. One of the applications that can be utilized for digital analysis is OneCeph. This application’s accuracy for cephalometric analysis, therefore, needs to be evaluated. This study aims to determine the differences in cephalometric measurements using the Ricketts method between hand tracing and digital tracing based on the OneCeph Android application. This analytic observational study utilized a cross-sectional design conducted at the Dental Hospital of UMY. The samples were 30 lateral cephalometric radiographs of good quality and had film negatives and digital files. The Ricketts method analysis was carried out manually and digitally utilizing the OneCeph application. The Shapiro Wilk test results showed that the data were normally distributed for all components except for the convexity of point A, lower incisor to A Pog line, and e-line. Comparative test results with independent sample t-test and Mann-Whitney test demonstrated no significant difference in all components (p0.05), except for the variable lower incisor to A Pog line (p0.05). The multivariate analysis results also showed p0.05, demonstrating no significant difference for all components (p0.05). The OneCeph application is no different from the gold standard (hand tracing/manual method) that has been used so far, so it can be an alternative for cephalometric tracing.